Weaving the Boundary - Wood, Karenne, 1960- (Book collections on Project MUSE., 2016)
"This is a book of poems that explores through verse the complex relationship and seismic rifts between indigenous historical perspectives and their colonizers' often misconstrued versions of history"--Provided by publisher.